2009
DOI: 10.1590/s0104-14282009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-mecânica de filmes de borracha natural epoxidada curáveis em temperatura ambiente

Abstract: Resumo: Neste trabalho é apresentado o estudo da formação de reticulações na temperatura ambiente, de borracha natural epoxidada (ENR) de 25% de grau de epoxidação, com um agente de cura contendo o tiol trimetilolpropano tris(2-mercaptoacetato) (TMP-SH). As composições foram realizadas a partir de solubilização da ENR e, posterior reação com o TMP-SH. Foram preparadas composições com 5, 10 e 20 phr de ENR e controles contendo NR e ENR. Também foi preparada uma composição com NR e 10 phr de TMP-SH para comprova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…On the other hand, this could be attributed to the structural changes induced in the ENR matrix during the blending process, which could lead to the formation of ether crosslinks and other epoxy ring products which are more prone to crosslinking processes, as stated in previous works found in literature . Moreover, these works showed that the increase in gel fraction of ENR is associated with the interchain interactions by H bonding through ring‐opened products of ENR such as hydroxyl group, hydrofuran, and carbonyl group formations and also by ether‐type crosslink formations . All these facts allowed the ENR matrix to present more free radicals and more possibilities to produce crosslinking than the NR rubber.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, this could be attributed to the structural changes induced in the ENR matrix during the blending process, which could lead to the formation of ether crosslinks and other epoxy ring products which are more prone to crosslinking processes, as stated in previous works found in literature . Moreover, these works showed that the increase in gel fraction of ENR is associated with the interchain interactions by H bonding through ring‐opened products of ENR such as hydroxyl group, hydrofuran, and carbonyl group formations and also by ether‐type crosslink formations . All these facts allowed the ENR matrix to present more free radicals and more possibilities to produce crosslinking than the NR rubber.…”
Section: Resultsmentioning
confidence: 72%
“…The introduction of epoxide groups within the polymer chain allows improvements of certain natural rubber properties such as oil resistance, gas impermeability, wet grip, and damping . For these reasons, this type of rubber, epoxidized natural rubber (ENR), is a subject of investigation as a potential substitute for several synthetic elastomers …”
Section: Introductionmentioning
confidence: 99%
“…The epoxide group is very reactive and is considered one of the most important intermediates in organic synthesis, as its introduction not only reduces the number of double bonds but also increases the rubber hydrophilicity. 6 Due to the high reactivity of the epoxide groups, they can be easily functionalized or modified by the attachment of bioactive compounds, in addition, these epoxidized groups increase the chemical compatibility between load-polymers or in physical polymer mixture. 7 As a new material, the PLGA/PIepox mixture has only a few works done and its properties, characteristics and processing possibilities have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Mixing epoxidized polyisoprene with other polymers is an alternative means of preparing biocompatible polymer blends with versatile characteristics and advanced mechanical properties for use in tissue engineering. 14 However, this technique requires careful in vitro study to analyze the potential risks and benefits that such a biomaterial can offer. 15…”
Section: Introductionmentioning
confidence: 99%